The kitchen - Rhodes, Gertrude (My University, 1898)
Introduction: From time immemorial, the kitchen has been an important factor of every household. Every lady knows the charm of a pleasant parlor. It is the “crown of the home,” but the kitchen is its heart. In the parlor may bloom the flower of its culture, but the room of its comfort is the kitchen. The parlor may reveal to us the exact standard of a woman’s taste, but the unerring interpretation of her disposition is the kitchen. It is for the woman of the nineteenth century to hold in her development the equal balance of physical and mental culture. She cannot do this and neglect her kitchen. No matter how far at times she may rise above it, it will always do her good to come back to it, and if it is the kitchen that it ought to be, she will ever feel delight in returning to its homely brightness and savory smells. It is the old New England kitchen which appeals to our ideas of comfort and beauty. It has a deep fireplace, a vast bake-oven, and a great pantry, whose wide shelves are filled with glittering mild pans all set for cream. There is also a store room, in which can be found all kinds of good things for everybody. The old kitchen floor is painted a clear gray, brightened by homemade mats. Colored prints are on the walls, an old-fashioned clock slowly ticks from its place in the corner, and there is a book-rack filled with books and magazines. An arm-chair, a sewing chair, and chintz covered lounge all combine to make it a comfortable room, and after all, it is only a kitchen with nothing in it too fine for its place.
Citation: Rhodes, Gertrude. The kitchen. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Kitchen; Fireplace; New England Kitchen; Pantry; Theses; Manuscripts (documents)